Androgen receptor signaling in the lungs mitigates inflammation and improves the outcome of influenza in mice. - Landon G Vom Steeg; Santosh Dhakal; Yishak A Woldetsadik; Han-Sol Park; Kathleen R Mulka; Emma C Reilly; David J Topham; Sabra L Klein (PLoS Pathogens)
Circulating androgens can modulate immune cell activity, but the impact of androgens on viral pathogenesis remains unclear. Previous data demonstrate that testosterone reduces the severity of influenza A virus (IAV) infection in male mice by mitigating pulmonary inflammation rather than by affecting viral replication. To examine the immune responses mediated by testosterone to mitigate IAV-induced inflammation, adult male mice remained gonadally intact or were gonadectomized and treated with either placebo or androgen-filled (i.e., testosterone or dihydrotestosterone) capsules prior to sublethal IAV infection. Like intact males, treatment of gonadectomized males with androgens improved the outcome of IAV infection, which was not mediated by changes in the control of virus replication or pulmonary cytokine activity. Instead, androgens accelerated pulmonary leukocyte contraction to limit inflammation. To identify which immune cells were contracting in response to androgens, the composition of pulmonary cellular infiltrates was analyzed and revealed that androgens specifically accelerated the contraction of total pulmonary inflammatory monocytes during peak disease, as well as CD8+ T cells, IAV-specific CD8+ T numbers, cytokine production and degranulation by IAV-specific CD8+ T cells, and the influx of eosinophils into the lungs following clearance of IAV. Neither depletion of eosinophils nor adoptive transfer of CD8+ T cells could reverse the ability of testosterone to protect males against IAV suggesting these were secondary immunologic effects. The effects of testosterone on the contraction of immune cell numbers and activity were blocked by co-administration of the androgen receptor antagonist flutamide and mimicked by treatment with dihydrotestosterone, which was also able to reduce the severity of IAV in female mice. These data suggest that androgen receptor signaling creates a local pulmonary environment that promotes downregulation of detrimental inflammatory immune responses to protect against prolonged influenza disease.